SEASONAL VARIATION IN SPECIES ABUNDANCE, DIVERSITY AND COMPOSITION OF FISH FAUNA IN LAGOS LAGOON, NIGERIA - OLUWAJOBA, E.O.; FAKAYODE, O.S; OLUBOBA, T.F.; WILLIAMS, A.B; UKAONU, S.U.; FOLA-MATTHEWS, O.O. (Nigerian Journal of Fisheries, 2017)
The seasonal variation in species abundance and composition of fish fauna of Lagos Lagoon were studied monthly from January to December, 2013. A total of 11,332 fish specimens made up of juveniles and adults caught were identified. They comprised of forty-nine species belonging to 28 families. Ethmalosa fimbriata (27.4 %) had the highest in terms of number followed by Chrysichthys nigrodigitatus (11.4 %). Twelve species occurred only once during the period of study. The fish reported in this study were group into three; first group were caught during the rainy season, second group were caught during the dry season, and the third group were caught throughout the year. The largest catch was recorded in May (51.05 kg) followed by July (45.34 kg). The least catch was recorded in January; dry season (4.5 kg). The mean value of water temperature (29.8 ℃), salinity (7.49 ‰), pH (7.17), dissolved oxygen (5.49 mg/L) and turbidity (5.68 NTU) were recorded. The results from this work will be a useful contribution to the current knowledge of fisheries needed for proper management and conservation of fisheries resources of Lagos lagoon. Key words: ,,